A carbonate reservoir model for Petersilie field in Ness County, Kansas: effective waterflooding in the Mississippian System - McCaw, Alyson Siobhan (Kansas State University, 2015)
The Petersilie oil field in Ness County, Kansas produces out of the Mississippian System, a reservoir composed mainly of shallow water carbonates, at depths of around 4375 ft (1334 m). The lithology of the field ranges from limestone to dolomite, to interlaminated limestone-dolomite beds. Chert is commonly found throughout. Petersilie field lies to the west of the Central Kansas Uplift, and to the east of the Hugoton Embayment. The field saw much drilling activity in the 1960’s, when it reached a production peak of nearly 378,000 barrels of oil per year. Production declined swiftly after that until the late 1990’s, when waterflooding was successfully employed. In this study, a reservoir model was produced for the Mississippian as it occurs in Petersilie field using the Department of Energy’s EdBOAST reservoir modeling software, with the intent of providing a reference for future drilling activity in the Mississippian and determining reservoir characteristics that may have contributed to the effectiveness of waterflooding in this area. The reservoir model was checked by simulation with a companion reservoir simulator program, BOAST 98. Subsequent comparison of simulated and actual oil production curves demonstrates the reliability of well log and drill stem test data for the field and proves the reservoir model to be a good fit for the Mississippian in Petersilie. Production curve analysis of Petersilie indicates the field was an ideal candidate for waterflooding because it has a solution-gas drive mechanism. As the field approached depletion from primary recovery, oil saturations remained high. Petersilie also exhibits high porosity and good permeability. The BOAST software was found to be an effective and inexpensive means for understanding the Mississippian reservoir in central to south-central Kansas. It was determined that BOAST has potential for practical use by smaller independent oil companies targeting the Mississippian in Kansas.
Keywords: Carbonate reservoir; Mississippian system; Reservoir model; Reservoir simulation; Waterflooding; Water injection; Geology (0372); Geophysical engineering (0467); Geophysics (0373)